Feedforward control of lateral asymmetries in heavy-plate hot rolling using vision-based position estimation. Issue 1 (July 2017) - Prinz, Katharina; Schausberger, Florian; Steinboeck, Andreas; Kugi, Andreas
Abstract: This paper presents a feedforward control concept for lateral asymmetries in heavy-plate hot rolling. A lateral off-center plate position generally entails asymmetric rolling forces, asymmetric mill stretch, and thus a wedge-shaped exit thickness that may cause a cambered plate contour and a rotatory motion of the plate. In this paper, a model of the mill stand and of the plate movement is presented. The model demonstrates that the plate movement in the reversing mill can be unstable and may cause the plate to collide with the mill housing in the worst case. The developed control concept makes use of the measurement of the shape and the position of the plate by an infrared camera. The controller compensates asymmetric deflections of the two sides of the mill stand associated with laterally asymmetric rolling forces caused by an off-centered plate position. Both simulations and long-term operation results at an industrial rolling mill confirm the robustness of the proposed control concept and show an improvement of the accuracy of the plate contour.